Of God and Reason in XVIII C. British North America - Acosta Gastélum, Carlos (México y la Cuenca del Pacífico, 2021)
The following article intends the description of the religious and intellectual environment in prerevo-lutionary America. It is divided into two main sec-tions: (1) a religious one where I will cover the most significant elements, and the ideological context of what was the most decisive cultural force in the formation of the new country ?Puritanism?; and (2) another that succinctly describes the particular shape that enlightened thought acquired in that part of the British Empire. A description of eighteenth-century Puritan North America requires a closer look at the ver-sion of Calvinism prevalent in the Northeastern seaboard, and therein to the cultural phenomenon of religious revivalism. Now connected to these variables lie a series of theological conceptions that shaped Puritan belief and practice in manifold ways, and that will be covered in the first section of this work: Arminianism, Antinomianism, Millen-nialism, and Religious Enthusiasm, among others.